Temperature and Frequency Dependent Permeability of Spinel Type Li-Cd Ferrite (Journal of Bangladesh Academy of Sciences, 2010)
A series of Li-Cd ferrite samples of composition Li0.5-x/2CdxBi0.02Fe2.48-x/2O4 for x = 0.0 to 0.7 were prepared by conventional double sintering ceramic technique. From temperature dependent permeability, μ′ at T=TC indicates that the samples have high homogeneity according to Globus et al. The Curie temperature, TC is found to decrease with increasing Cd content. The sample with x=0.7 shows anomalous temperature dependent magnetic ordering. Initial permeability, μ′ and magnetic loss factor, tanδ have been investigated up to 13 MHz frequency range. Frequency dependent permeability increase except x = 0.7 with Cd content and also increase with sintering temperature. The magnetic loss factor is minimum at frequency around 1 MHz and rises sharply beyond that frequency. Key words: Lithium ferrite, Curie temperature, Initial permeability, Loss factor. DOI: 10.3329/jbas.v33i2.4099 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 159-166, 2009